Alloantibodies in von Willebrand Disease - Franchini, Massimo; Mannucci, Pier Mannuccio (Seminars in Thrombosis and Hemostasis, 2018)
von Willebrand disease (VWD), the most commonly known inherited bleeding disorder, is caused by a partial (type 1) or total (type 3) deficiency or dysfunction (type 2) of von Willebrand factor (VWF). Its management encompasses the prevention or treatment of bleeding by raising endogenous VWF levels using a synthetic agent, such as desmopressin, or providing exogenous VWF concentrates. The development of inhibitory alloantibodies against VWF is a rare but often severe complication encountered during the treatment of type 3 VWD, which is associated with a lack of hemostatic response to infused VWF concentrates and more rarely with allergic, even anaphylactic, reactions. This narrative review will focus on the characteristics of such alloantibodies and their management, which can be very challenging for physicians operating at hemophilia treatment centers.
Keywords: von Willebrand disease; type 3; alloantibodies; anaphylaxis